COORDINATION OF INTERNAL HEMODYNAMIC DISORDERS IN PATIENTS WITH CHRONIC KIDNEY DISEASE OF DIABETIC GENESIS BY USING 2ND TYPE SODIUM-GLUCOSE COTRANSPORTER INHIBITORS - Uzakova N.I. (Central Asian Journal of Medicine, 2025)
The article presents the results of the research on the alternative treatment of intrarenal hemodynamic disorders with the use of type 2 sodium-glucose cotransporter inhibitors in 103 patients with chronic kidney disease developed on the basis of diabetic nephropathy. Also, comparing the obtained results with the results of other authors’ researches, the nephroprotective effect of the drug is once again based in detail.